Functional food products in Japan: A review - Shun Iwatani; Naoyuki Yamamoto (Food Science and Human Wellness)
Japan has a long history of using foods with health benefits and Japanese people are well-known for their longevity. In 1991, the Ministry of Health, Labor and Welfare introduced a functional food regulation called “foods for specified health uses” (FOSHU) in Japan. After the introduction of the functional food system, many clinically proven FOSHU products with health benefits have been developed and launched in the market. As a result, the net sales of FOSHU products reached 6.2 billion dollars in 2007. Most of the health claims relate to improving gastro-intestinal health using probiotics. Triglycerides, high blood pressure, high LDL-cholesterol, and high blood glucose are mainly associated with the related health claims. After 2007, the market for FOSHU products was almost saturated. However, a novel functional regulatory system/called “Foods with Function Claims” was established in 2015 based on the Dietary Supplement Health and Education Act system established in the USA. Major health claims in the new regulation system are associated with fatigue, eyes, memory, stress, sleep, joints, blood flow, body temperature, muscles, and Body Mass Index. After the introduction of the new system, the total sales for functional foods including FOSHU products reached 8 billion dollars in 2018. The new functional regulatory system is more flexible in terms of health claims, the protocol for clinical studies, and the required results. Therefore, the market for new regulatory products is still growing. In the present paper, the potential of both regulatory systems and some related issues will be discussed. Keywords: Food for specified health uses, FOSHU, New Functional Foods, Foods with function claims, Consumer Affairs Agency, Approval